Scalable maps of random dots for middle-scale locative mobile games - Lu Chen; Hongbo Fu; Li, Wing Ho Andy; Chiew-Lan Taj (2013 IEEE Virtual Reality (VR), 2013)
In this work we present a new scalable map for middle-scale locative games. Our map is built upon the recent development of fiducial markers, specifically, the random dot markers. We propose a simple solution, i.e., using a grid of compound markers, to address the scalability problem. Our highly scalable approach is able to generate a middle-scale map on which multiple players can stand and position themselves via mobile cameras in real time. We show how a classic computer game can be effectively adapted to our middle-scale gaming platform.